The Potential of low-grade fluorite ore of Landi Kotal, Khyber Pakhtunkhwa Province, Pakistan - Bhatti, Muhammad Arif; Zafar, Uzma; Mehmood, Ansar; Mehmood, Rashid; Nasir, Saqib (Bangladesh Journal of Scientific and Industrial Research, 2023)
This paper describes the results of a beneficiation study conducted on low-grade fluorite ore. The study was aimed at the development of a suitable beneficiation process to produce chemical grade fluorite concentrate. The representative sample of the ore was up-graded by leaching and flotation process. The important parameters of froth flotation process were optimized to obtain highest grade and recovery of fluorite concentrate. A single-factor variation method was applied to get the optimum conditions of the process. The rougher concentrate was reground to liberate fine locked fluorite particles and two cleaning flotation were employed in close circuit to achieve higher grade concentrate. A process flowsheet was designed in the light of these tests. After optimization of process parameters, the fluorite ore containing 62.24% CaF2 could be upgraded to a concentrate assaying 97.55% CaF2 with an overall recovery of 92.73%. The prepared fluorite concentrate meets the specifications of chemical grade and is suitable for production of fluoride based chemicals. Bangladesh J. Sci. Ind. Res. 58(2), 107-118, 2023